Adaptogens in chemobrain (Part I): plant extracts attenuate cancer chemotherapy-induced cognitive impairment : transcriptome-wide microarray profiles of neuroglia cells - Seo, Ean-Jeong; Klauck, Sabine; Efferth, Thomas; Panossian, Alexander (Phytomedicine, 2019)
Background - Cancer chemotherapy-induced cognitive impairments are presumably associated with undesirable effects of chemotherapy on physiological functions of brain cells. Adaptogens are natural compounds or plant extracts increasing an organism's adaptability and survival in stress. They exhibited neuroprotective effects and increased cognitive functions in clinical studies in human beings. - Hypothesis - We hypothesized that selected adaptogenic plant extracts attenuate or prevent cancer chemotherapy-induced cognitive impairments. - Aim - We assessed the effects of selected adaptogenic herbal extracts on FEC (fixed combination 5-fluorouracil, epirubicin and cyclophosphamide) induced changes in transcriptome-wide RNA microarray profiles of neuroglia cells. The aim of the study was to predict potential effects of andrographolide, Andrographis herb, Eleutherococcus root genuine extracts, their fixed combination (AE) and the combination of Rhodiola roots, Schisandra berries and Eleutherococcus roots (RSE) on cellular and physiological, mostly cognitive functions. - Methods - Gene expression profiling was performed by transcriptome-wide mRNA microarray in the human T98G neuroglia cells after treatment with adaptogens. Interactive pathways downstream analysis was performed with data sets of significantly up- or down-regulated genes and predicted effects on cellular functions and diseases were identified by Ingenuity IPA database software. - Results - FEC deregulated 67 genes involved in decrease of neuronal development, 37 genes involved in development of the sensory system, 12 genes in extension of axons, and 3 genes in migration of neurons. Co-incubation with Andrographis paniculata (AP) suppressed FEC-induced deregulation of a large number of genes involved in predicted activation of neuronal death and inhibition of neurogenesis, and 16 genes related to inhibition of several functions in the nervous system. Co-incubation with AE suppressed FEC-induced deregulation of a number of genes involved in predicted inhibition of axon extension, migration of T98G neuroglia cells, conduction of nerves and other genes related to regulations of some other functions in the nervous system. - Conclusion - Application of cytostatic drugs in combination with apoptogenic plant extracts induced significant changes in transcriptome-wide mRNA microarray profiles of neuroglial cells. These changes indicate on potential beneficial effects on neuronal functions associated with mild cognitive impairments in cancer chemotherapy.